Longitudinal Network Stability of the Functional Impairment of Anxiety and Depression. (May 2018) - Curtiss, Joshua; Ito, Masaya; Takebayashi, Yoshitake; Hofmann, Stefan G.
Anxiety and depression are comorbid conditions with significant functional impairment. This study examines the temporal changes in the network structure of the functional impairment associated with anxiety and depression. A clinical sample ( n = 1, 667) of individuals from Japan completed a battery of self-report instruments to assess the degree and level of impairment of anxiety and depression. The network structure was estimated at two time points using partial correlation coefficients and the glasso regularization procedure. Several permutation tests were conducted to examine network changes over time. Global and individual features of the network were stable across time. Furthermore, depression was more central than anxiety at both time points. Results should be interpreted in light of cultural factors involving the Japanese sample. These results underscore the temporal stability of the functional impairment of anxiety and depression as well as the importance of depression in the overall comorbid network.